Neoadjuvant Endocrine Therapy Compared to Neoadjuvant Chemotherapy in Node-Positive HR+, HER2− Breast Cancer (Nodal pCR and the Rate of ALND): A Systematic Review and Meta-Analysis - Mahtab Vasigh; Mohammadreza Karoobi; Austin D. Williams; Fasika Molla Abreha; Richard J. Bleicher; Seyed Mostafa Meshkati Yazd; Tahereh Shamsi; Ramesh Omranipour; Ahmad Elahi; David Farhat; Mehran Habibi (The Breast Journal)
Introduction. Patients with hormone receptor-positive (HR+), HER2-negative (HER2−) breast cancers have the lowest response to neoadjuvant therapy of all subtypes. The role of neoadjuvant endocrine therapy (NET) in clinically node-positive (cN+), HR+, HER2− patients is evaluated in this meta-analysis. Methods. This study was performed between January 2010 and August 2022. We evaluated the node pathologic complete response (pCR) and axillary lymph node dissection (ALND) rates after neoadjuvant endocrine therapy (NET). Results. 18,037 HR+, HER2−, cN+ stage II and stage III breast cancer patients within eleven studies received neoadjuvant treatments. 3,707 (20.6%) patients received NET and 14,330 (79.4%) received NAC. The average age of the NET patients was higher than that of the neoadjuvant chemotherapy (NAC) patients (64.1 versus 47.6 years old, p<0.001). 45.0% and 26.9% of the NET and the NAC groups underwent a lumpectomy. The pooled estimates of node pCR in NET and NAC groups were 8.9% and 14.9%, and the pooled proportion of ALND was 39.1% and 58.5%, respectively. Conclusion. The rate of node pCR was lower among cN+ patients who received NET compared to the NAC group. The rate of ALND among cN+ NET patients was lower than the NAC group, revealing more patients with residual nodal disease do not get ALND in the NET group. Further prospective studies are required to compare survival outcomes as a more reliable surrogate.